A new species and new record of deep-sea scale-worms (Polynoidae: Polychaeta) from the Okinawa Trough and the South China Sea - Sui, Jixing; Li, Xinzheng (Zootaxa, 2017)
A new species of scale-worm, Lepidonotopodium okinawae sp. nov. from the Okinawa Trough is described. The new species differs from the other species of Lepidonotopodium by having 24 segments and numerous foveolae on the surface of elytra with one globular micropapilla in every foveola. A new record of the mussel commensal Branchipolynoe pettiboneae Miura & Hashimoto, 1991 is reported and described from the northern South China Sea, where for the first time the scale-worm is noted as occurring at a cold-seep. Keys to distinguish the species of Branchipolynoe and Lepidonotopodium are provided.